POSTOPERATIVE RECOVERY FROM UNILATERAL BLINDNESS CAUSED BY TUBERCULUM SELLAE MENINGIOMA - OYAMA, HIROFUMI (Nagoya J Med Sci, 2012)
A 47-year-old female had noticed diminished visual acuity in both eyes 2 months previously. The patient had vision loss (no light perception) in her right eye on admission. Her left visual acuity was 1.2 (naked vision) and an upper temporal quadrant hemianopsia was revealed in her left eye. Optic disc atrophy was also found bilaterally during a fundus examination. The tumor was located at the tuberculum sella. The first operation was performed using a right pterional approach. The right optic nerve was thin and atrophic and was severely encased by the tumor. Considering the deterioration of her visual evoked potential, the operation was terminated in the remaining major part of the tumor. Postoperatively, the patient suffered visual loss in her right eye (no light perception), decreased visual acuity (naked: 0.6 (corrected: 1.0)), and deteriorated visual field defects (upper temporal quadrant hemianopsia) in her left eye. The tumor remnant was resected again 2 weeks later using the right frontobasal and pterional approaches. The tumor around the bilateral internal carotid arteries and optic nerves was not resected. Light perception in the right eye appeared 2 weeks after the operation. Although an opthalmological examination revealed right optic atrophy, finger counting was possible in the upper nasal visual field of the right eye three months after the second operation. Her visual acuity was 0.7 (1.0), and the upper temporal quadrant hemianopia of the left eye improved in comparison with the preoperative one. Our case demonstrated the possibility of a recovery from blindness.